2021
DOI: 10.3332/ecancer.2021.1288
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pre-operative lymphocyte to monocyte ratio and serum cancer antigen-125 among women with epithelial ovarian cancer in Lagos, Nigeria

Abstract: Ovarian cancer (OC) is the second most common genital cancer worldwide, and the most lethal of all genital cancers. The role of inflammation and markers of systemic inflammation such as neutrophils, lymphocytes and monocytes in cancer biology have been investigated and reported in many studies. Cancer antigen 125 (CA-125) is currently in use as an adjunct to diagnosis, prognostication and monitoring of epithelial OC (EOC). This test is not readily available in many centres in sub-Saharan Africa, creating a nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Our study showed that a high NLR may promote the proliferation and metastasis of ovarian cancer cells, manifested by an increased FIGO staging, lymph node metastasis, and ascites, which ultimately lead to a poor prognosis. These findings have been confirmed by several previous studies ( 21 , 22 ). In addition, studies have also shown that a high NLR is associated with the sensitivity of chemotherapy drugs in patients with ovarian cancer, which is manifested by patients with a high NLR reacting less after receiving chemotherapy ( 9 , 10 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that a high NLR may promote the proliferation and metastasis of ovarian cancer cells, manifested by an increased FIGO staging, lymph node metastasis, and ascites, which ultimately lead to a poor prognosis. These findings have been confirmed by several previous studies ( 21 , 22 ). In addition, studies have also shown that a high NLR is associated with the sensitivity of chemotherapy drugs in patients with ovarian cancer, which is manifested by patients with a high NLR reacting less after receiving chemotherapy ( 9 , 10 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the latter, calculating MLR prior to surgical intervention could be of clinical value in predicting stage, grade, and metastasis. Additionally, MLR was associated with serum CA-125 levels in a retrospective, cross-sectional study of Nigerian ovarian cancer patients [ 63 ]. Furthermore, MLR performed better than NLR in predicting the progression and overall survival of bladder cancer patients [ 64 , 65 , 66 , 67 ], and was invaluable for the prognosis and survival of cervical cancer and non-small-cell lung cancer patients [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%